Functional stress imaging to predict abnormal coronary fractional flow reserve: the PACIFIC 2 study . (16th June 2022) - Driessen, Roel S; van Diemen, Pepijn A; Raijmakers, Pieter G; Knuuti, Juhani; Maaniitty, Teemu; Underwood, S Richard; Nagel, Eike; Robbers, Lourens F H J; Demirkiran, Ahmet; von Bartheld, Martin B; van de Ven, Peter M; Hofstra, Leonard; et al.
Abstract: Aims: The diagnostic performance of non-invasive imaging in patients with prior coronary artery disease (CAD) has not been tested in prospective head-to-head comparative studies. The aim of this study was to compare the diagnostic performance of qualitative single-photon emission computed tomography (SPECT), quantitative positron emission tomography (PET), and qualitative magnetic resonance imaging (MRI) in patients with a prior myocardial infarction (MI) or percutaneous coronary intervention (PCI). Methods and results: In this prospective clinical study, all patients with prior MI and/or PCI and new symptoms of ischaemic CAD underwent 99m Tc-tetrofosmin SPECT, [ 15 O]H2 O PET, and MRI, followed by invasive coronary angiography with fractional flow reserve (FFR) in all coronary arteries. All modalities were interpreted by core laboratories. Haemodynamically significant CAD was defined by at least one coronary artery with an FFR ≤0.80. Among the 189 enrolled patients, 63% had significant CAD. Sensitivity was 67% (95% confidence interval 58–76%) for SPECT, 81% (72–87%) for PET, and 66% (56–75%) for MRI. Specificity was 61% (48–72%) for SPECT, 65% (53–76%) for PET, and 62% (49–74%) for MRI. Sensitivity of PET was higher than SPECT ( P = 0.016) and MRI ( P = 0.014), whereas specificity did not differ among the modalities. Diagnostic accuracy for PET (75%, 68–81%) did not statistically differ from SPECT (65%, 58–72%, P = 0.03) and MRI (64%, 57–72%, P = 0.052). Using FFR < 0.75 as a reference, accuracies increased to 69% (SPECT), 79% (PET), and 71% (MRI). Conclusion: In this prospective head-to-head comparative study, SPECT, PET, and MRI did not show a significantly different accuracy for diagnosing FFR defined significant CAD in patients with prior PCI and/or MI. Overall diagnostic performances, however, were discouraging and the additive value of non-invasive imaging in this high-risk population is questionable. Structured Graphical Abstract: Structured Graphical Abstract In this prospectively conducted study, every patient underwent myocardial perfusion imaging with SPECT, PET, and MRI (left panel) with subsequent ICA and FFR measurements in all vessels regardless of imaging results and stenosis severity (middle panel). This resulted in modest diagnostic performances of whom PET revealed the greatest AUC on a per-patient and per-vessel level (right panel). In this case example, qualitative SPECT shows a reversible defect during stress in the inferior wall with an SDS of 5. The quantitative PET polar map depicts abnormal absolute myocardial blood flow during stress in the RCA territory of 1.22 mL/min/g myocardial tissue, indicative for ischaemia. Qualitative MRI showed a stress perfusion defect without myocardial scar, suggestive of ischaemia in the inferior wall. The ICA revealed a haemodynamically significant lesion in the proximal RCA as indicated by an abnormal FFR of 0.44. AUC, area under the receiver operating characteristic curve; Cx, circumflex artery; FFR, fractional flow reserve; ICA, invasive coronary angiography; LAD, left anterior descending artery; MRI, magnetic resonance imaging; PET, positron emission tomography; RCA, right coronary artery; ROC, receiver operating characteristic curve; SDS, summed difference score; and SPECT, single-photon emission computed tomography.